The place beyond the lines - Efficient storage allocation in a spatially unbalanced power system with a high share of renewables - Berit Hanna Czock; Amelie Sitzmann; Jonas Zinke (Institute of Energy Economics at the University of Cologne (EWI), 2023)
Increasing shares of wind and solar generation serve to decarbonize electricity generation; however, their temporal and spatial variability poses challenges in grid operation. While grid expansion is restricted in the medium term, storage technologies can potentially increase the power systems' efficiency by temporally aligning generation and demand and increasing network utilization. This paper uses a theoretical and a numerical model to evaluate the optimal allocation of battery storage. In a case study for Germany, we find that batteries can reduce system costs when placed behind the north-south grid bottleneck and near solar power. The supply costs in a setting with uniform prices and a random battery distribution are 9.3% higher than in the theoretical first-best benchmark with nodal prices. An optimal allocation of batteries can reduce this efficiency gap by 0.7 percentage points to 8.6%. This corresponds to almost a doubling of the supply cost savings per euro spent on battery installation. Due to a lack of spatially differentiated investment incentives under the German uniform pricing scheme, batteries have to be allocated by additional policies. Simple allocation rules such as tying battery siting to solar capacity or explicitly identifying a limited number of suitable sites and auctioning capacity can approximate an optimal allocation.
Keywords: D47; D61; C61; Q40; 330; Market Design; Electricity Markets; Nodal Pricing; Energy System Modeling; Renewable Energies; Storage; Flexibility; Batteries